Ensino médio politécnico no RS: desafios e possibilidades - Maia, Átila de Macedo (2015)
This research, linked to the Research Field School Practices and Public Policies of PPGE / UFSM, aims to understand the operating procedures of the Integrated Seminars in two high schools of the State Public Network in Santa Maria / RS. To develop this research, we propose to answer the question: How do the changes that are being implemented in high school, based on public policy, and documents such as the Law of Guidelines and Bases for Secondary Education (LDB / 96), National Curriculum Guidelines for Secondary Education (DCNEM / 2012) and pedagogical proposal to the Polytechnic High School and Professional Education Integrated to high school, we will call PREM / RS, are altering the views of teachers and students of partner schools of research and how to establish the interdisciplinary work in Integrated Seminars in schools. It brings out your weaknesses, challenges and possibilities of a proposal. Data were collected, analyzed and tabulated based on interviews with teachers and high school students from partner schools. In the training of teachers, it is argued on the need for greater promotion of training, both initial and continued articulated with the school and restructuring teaching practices. The data indicate that it is challenging the implementation of the PREM / RS, whether in individual or curricular aspects but mainly a resizing of time and school spaces. The analysis was performed according to the crossing of data, creation of hypotheses and a discussion with authors in an attempt to create a relationship between the data and the facts present in the education of our state, post-implementation of the PREM / RS. Authors who do the theoretical discussion interface are: MOEHLECKE (2002); SAVIANI (1994); SANTOME (1998); ROMANELLI (1997); FRIGOTTO (2009); JAPIASSU (1976); GRAMSCI (1978); KUENZER (1995, 2000, 2005, 2013): POMBO (2005, 2008), among others. Therefore, we believe that the discussion permeated by relevant theoretical contributes the results achieved with respect to the concepts of polytechnic, interdisciplinary and high school, this Master's dissertation.